Conductive heating plate for hair straightener and preparation process of conductive heating plate

Through the graphene composite mixed liquid and modified doped three-dimensional structure boron nitride, conductive heating plates for hair straighteners were prepared, which solved the problems of slow heating speed of existing conductive heating plates and easy material damage, and achieved the Quickly warm up and safe use effect.

CN119300187AActive Publication Date: 2025-01-10SHENZHEN DELONG ELECTRICAL APPLIANCE CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411828803.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-01-10
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The heating speed of the existing hair straightener conductive heating plate is slow, and it is easy to cause temperature control of the heating body during frequent use, damage to the plastic material that fixes the heating plate, affecting the use effect and safety.

Method used

Using the combination technology of graphene composite mixed liquid, modified doped three-dimensional structure boron nitride, thermally conductive insulating layer and thermally insulating layer, the conductive heating plate is prepared through electrospinning and compressing processes to improve the conductive and thermal insulation performance. Ensure the stability and safety of the heating layer.

Benefits of technology

It achieves rapid heating and improves thermal conductivity, avoids excessive temperature of the heating body to damage the fixed material, enhances the safety and comfort of the hair straightener, and reduces energy waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119300187A_ABST
    Figure CN119300187A_ABST
Patent Text Reader

Abstract

The invention provides a conductive heating plate for a hair straightener and a preparation process of the conductive heating plate, and belongs to the technical field of conductive heating plate preparation. The preparation process comprises the following steps: preparing a graphene composite mixed solution; preparing the modified boron nitride doped with the three-dimensional structure; preparing a heat-conducting insulating layer; preparing a heat insulation layer; and preparing the conductive heating plate. The conductive heating plate is prepared from the ceramic substrate, the heat conduction insulating layer, the graphene composite heating layer, the conductive layer and the heat insulation insulating layer in sequence from bottom to top, and in the frequent heating and cooling circulation process of the hair straightener, the graphene composite heating layer can keep the performance unchanged; the heating effect is not affected by material aging or performance attenuation, the heat insulation layer serving as the outermost layer of the conductive heating plate can isolate heat generated by the heating body, and the heat is effectively prevented from being transmitted to a shell, a handle and other parts of the hair straightener.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of conductive heating plate preparation, and in particular to a conductive heating plate for a hair straightener and a preparation process thereof. Background Art

[0002] As people's demands for personal image and hairstyle management continue to increase, hair straighteners, as a common hairdressing tool, have been widely used in the market. Its working principle is mainly to generate heat through a conductive heating plate, and use the heat to change the shape of the hair, thereby achieving a straight hair effect.

[0003] In the prior art, the heating elements in the conductive heating plate of a hair straightener are usually mostly ceramic heating elements and PTC heating elements. Ceramic heating elements have a faster heating speed. Generally, the surface temperature of the clamping plate can reach about 200 degrees in 30 to 45 seconds, which can quickly meet the needs of straightening hair. However, the ceramic heating element is sintered at a high temperature of more than 1000 degrees. Once the circuit loses control, its temperature will quickly exceed 300 degrees, which is easy to burn the plastic material that fixes the heating plate and cause the heating plate to fall off; and the PTC heating element temperature reaches 200 degrees slowly, generally taking about one and a half to two minutes, and during use, it cannot be maintained at a high temperature like a ceramic heating element, so the effect of straightening hair is relatively poor, and the existing hair straightener will cause the heating element to heat up more slowly during frequent use, so it takes longer to preheat, affecting the user experience.

[0004] Therefore, we propose a conductive heating plate for a hair straightener and a preparation process thereof, aiming to solve the problems of slow heating speed and easy burning of the plastic material fixing the heating plate in the existing heating element in the application of hair straighteners. Summary of the invention

[0005] In view of the deficiencies in the prior art, an object of the present invention is to provide a conductive heating plate for a hair straightener and a preparation process thereof.

[0006] A preparation process of a conductive heating plate for a hair straightener, comprising the following steps: S1: Preparation of graphene composite mixture Polyvinyl alcohol, sodium carboxymethyl cellulose and sodium dodecylbenzene sulfonate are used as a mixed liquid, and then a conductive dispersion prepared by onion carbon, modified graphene oxide and polyacrylonitrile is added, and the graphene composite mixed liquid is prepared after mixing; S2: Preparation of modified doped three-dimensional boron nitride A three-dimensional boron nitride is prepared by using a sodium chloride template, the three-dimensional boron nitride is modified by a silane coupling agent, and then modified by plasma carbon doping to obtain a modified doped three-dimensional boron nitride; S3: Preparation of thermally conductive insulating layer The modified nano-aluminum oxide and the modified doped three-dimensional structured boron nitride are used as thermal conductive fillers, and then 4,4'-diaminodiphenyl ether and pyromellitic anhydride are added to prepare a spinning solution for electrostatic spinning to obtain a thermal conductive insulating spinning membrane, which is then immersed in a reaction glue solution composed of 4,4'-diaminodiphenyl ether, N,N'-dimethylacetamide solution and pyromellitic anhydride, and finally vacuum dried to obtain a thermal conductive insulating film, i.e., a thermal conductive insulating layer; S4: Preparation of thermal insulation layer The thermal insulation gel is prepared by using benzophenone oxadiazine monomer, ZIF-L powder and tetraethyl orthosilicate as raw materials, namely the thermal insulation layer; S5: Preparation of conductive heating plate A graphene composite heating layer is prepared by using a graphene composite mixed liquid, and a ceramic substrate, a thermal conductive insulating layer, a graphene composite heating layer, a conductive layer and a thermal insulating layer are stacked in sequence from bottom to top and pressed with a pressing machine to obtain a conductive heating plate.

[0007] Furthermore, step S1 of preparing the graphene composite mixed solution specifically comprises the following steps: S1.1: Add 2-3 parts by weight of polyvinyl alcohol and 0.3-0.5 parts by weight of sodium carboxymethyl cellulose to 80-100 parts by weight of deionized water, and then add 0.2-0.3 parts by weight of sodium dodecylbenzene sulfonate, and stir and mix at 80-85° C. for 2-3 hours to obtain a mixed solution; S1.2: Add 2-3 parts by weight of onion carbon and 5-8 parts by weight of modified graphene oxide to 50-60 parts by weight of N,N-dimethylamide, mix them ultrasonically at room temperature for 30-40 minutes, then add 12-15 parts by weight of polyacrylonitrile, stir and mix at 60-65°C for 24-25 hours to obtain a conductive dispersion; S1.3: Add the conductive dispersion into the mixed solution, stir and mix at 70-75°C for 6-8h, then cool and let stand for 24-25h to obtain a graphene composite mixed solution.

[0008] Furthermore, step S2 of preparing modified doped three-dimensional structured boron nitride specifically comprises the following steps: S2.1: 12-13 parts by weight of saturated sodium chloride is added to 20-22 parts by weight of alcohol, and then vacuum filtered and dried to obtain micron sodium chloride crystals, 10-12 parts by weight of micron sodium chloride crystals and 2-3 parts by weight of boron trioxide are mixed and placed in an alumina crucible, and then the alumina crucible is placed in a tube furnace, argon gas is introduced, and heated to 500-520°C at 10-12°C / min; S2.2: After 500-520°C, turn off the argon gas, introduce ammonia, continue heating to 700-720°C, keep warm for 20-30 minutes, heat again to 1100-1200°C, keep warm for 10-20 minutes, cool to room temperature, wash the obtained precipitate with deionized water, then vacuum filter and dry, and dry at 60-65°C for 10-12 hours to obtain three-dimensional boron nitride; S2.3: Add 3-5 parts by weight of three-dimensional boron nitride to 10-12 parts by weight of anhydrous ethanol, stir for 20-30 minutes at 50-60°C under ultrasonic conditions and 5000-6000 r / min, then add 0.2-0.3 parts by weight of 20-30wt% silane coupling agent KH560 aqueous solution, continue stirring for 40-50 minutes, then place in an oven at 60-70°C to dry, grind and crush to obtain silane coupling agent modified three-dimensional boron nitride; S2.4: Place the silane coupling agent modified three-dimensional boron nitride in a plasma reaction device, evacuate to -2800 kPa to -3000 kPa, then introduce ethylene and nitrogen to -2000 kPa to -2200 kPa, then evacuate to -2800 kPa to -3000 kPa again, then introduce ethylene and nitrogen to -1300 kPa to -1500 kPa, finally evacuate to -2800 kPa to -3000 kPa again, and perform plasma discharge at a voltage of 28-30 kV and a frequency of 9-10 kHz for 15-20 minutes to obtain modified doped three-dimensional boron nitride.

[0009] Furthermore, in step S2.4, the weight ratio of ethylene to nitrogen is 1-2:25.

[0010] Furthermore, step S3 of preparing the thermally conductive insulating layer specifically includes the following steps: S3.1: Add 0.02-0.05 parts by weight of silane coupling agent KH550 to 100-120 parts by weight of ethanol, then add glacial acetic acid to adjust the pH value to 3-4, hydrolyze for 20-30 minutes, add 2-3 parts by weight of nano-alumina, mix by ultrasonic for 1-2 hours, and stir in a water bath at 70-80°C for 2-3 hours, filter, wash with anhydrous ethanol 2-3 times, and dry to obtain modified nano-alumina; S3.2: Add 0.2-0.3 parts by weight of modified nano-aluminum trioxide and 0.5-0.7 parts by weight of modified doped three-dimensional structure boron nitride to 20-30 parts by weight of N, N'-dimethylacetamide solution, and mix under ultrasonic stirring for 8-10 hours. In a nitrogen atmosphere, add 1-2 parts by weight of 4,4'-diaminodiphenyl ether, and mix under stirring for 20-30 minutes. Then, add pyromellitic anhydride three times under ice bath conditions, adding 0.3-0.5 parts by weight of pyromellitic anhydride each time, and mix under stirring for 20-30 minutes to obtain a spinning solution. Perform electrostatic spinning at a spinning voltage of 20-22 kV, a receiving distance of 20-22 cm, and a push injection speed of 0.8-0.9 mm / min to obtain a thermally conductive insulating spinning membrane; S3.3: Dissolve 2-3 parts by weight of 4,4'-diaminodiphenyl ether in 50-60 parts by weight of N,N'-dimethylacetamide solution, then add 2-3 parts by weight of isophthalic anhydride, react for 4-5 hours to obtain a reaction colloid, immerse the thermally conductive insulating spinning membrane in the reaction colloid for 4-5 hours, and then vacuum dry it to obtain a thermally conductive insulating film, which is the thermally conductive insulating layer.

[0011] Furthermore, step S4 of preparing the heat-insulating layer specifically comprises the following steps: S4.1: 4-5 parts by weight of zinc nitrate hexahydrate and 16-18 parts by weight of 2-methylimidazole are added to 500-520 parts by weight of deionized water respectively, and the mixture is stirred and dissolved for 4-5 hours to obtain a zinc nitrate hexahydrate solution and a 2-methylimidazole solution; S4.2: Add the zinc nitrate hexahydrate solution to the 2-methylimidazole solution, continue stirring and mixing for 4-5 hours, then centrifuge at 8000-9000 r / min, filter to obtain a precipitate, wash the precipitate with deionized water and dry to obtain ZIF-L powder; S4.3: Add 2-3 parts by weight of benzoxazine monomer to 60-70 parts by weight of N,N-dimethylformamide solution, stir to dissolve, then add 2-3 parts by weight of 2 mol / L hydrogen chloride solution, stir and mix for 10-12 minutes, then add 12-15 parts by weight of tetraethyl orthosilicate, continue to stir and mix for 20-30 minutes, finally add 0.2-0.5 parts by weight of ZIF-L powder, and ultrasonically disperse for 1-2 hours to obtain a thermal insulation gel solution; S4.4: Inject the thermal insulation gel solution into a polypropylene tank to seal the gel. The gel time is 7-8 hours, followed by aging for 48-50 minutes. Finally, solvent replacement and normal pressure drying are performed to obtain the thermal insulation gel, which is the thermal insulation layer.

[0012] Furthermore, the preparation of the conductive heating plate in step S5 specifically includes the following steps: S5.1: The graphene composite mixed solution is electrospinned to form a composite film, wherein the distance between the needle tip and the collecting device during electrospinning is 15-18 cm, the voltage is 15-16 kV, and the injection speed is 0.5-0.8 mm / min. The composite film is then heated at 280-300° C. for 2-3 h, and then kept at 700-800° C. for 10-12 min in a nitrogen atmosphere to obtain a graphene composite heating layer; S5.2: Use an etcher to etch the designed circuit onto the conductor circuit layer, then print the cured electronic paste onto the circuit of the conductor circuit layer, and form a conductive layer after curing at 180-200℃ for 10-20min. Stack the ceramic substrate, thermal conductive insulation layer, graphene composite heating layer, conductive layer and thermal insulation layer in sequence from top to bottom and press them with a press to obtain a composite board. The pressing temperature is controlled at 300-320℃ to obtain a conductive heating plate.

[0013] Furthermore, the ceramic substrate in step S5.2 is one of an aluminum oxide ceramic substrate and an aluminum nitride ceramic substrate.

[0014] Furthermore, in step S5.2, the conductor line layer is made of one of copper, aluminum, copper foil and aluminum foil materials.

[0015] A conductive heating plate for a hair straightener is prepared by any of the above-mentioned processes for preparing a conductive heating plate for a hair straightener.

[0016] Compared with the prior art, the present invention has at least the following beneficial effects: 1. The present invention adopts a ceramic substrate, a heat-conducting insulating layer, a graphene composite heating layer, a conductive layer and a heat-insulating insulating layer to prepare a conductive heating plate in order from bottom to top. During the frequent heating and cooling cycles of the hair straightener, the graphene composite heating layer can maintain its performance unchanged, and the heating effect will not be affected by aging or performance degradation of the material. As the outermost layer of the conductive heating plate, the heat-insulating insulating layer can isolate the heat generated by the heating element, effectively preventing the heat from being transferred to the outer shell and handle of the hair straightener. During the operation of the hair straightener, it can concentrate the heat in the heating plate area, improve the utilization efficiency of heat, and reduce energy waste. At the same time, it can also prevent the user from being scalded by touching the overheated part when operating the hair straightener, thereby improving the safety and comfort of the hair straightener.

[0017] 2. The present invention adds a conductive dispersion to the mixed solution and then performs electrostatic spinning. Polyvinyl alcohol and sodium carboxymethyl cellulose can adjust the viscosity of the graphene composite mixed solution, which is helpful for the formation of fibers during the electrostatic spinning process. Graphene and onion carbon can be evenly distributed in the polyacrylonitrile carbonized fiber, which can avoid uneven performance caused by local agglomeration. In a high-temperature nitrogen environment, polyacrylonitrile is carbonized to form a carbonaceous structure. After being doped with onion carbon and graphene, it forms a complex three-dimensional network structure with the carbonaceous structure. The carbonized polyacrylonitrile, onion carbon and graphene cooperate with each other to provide more transmission channels and scattering centers for electrons, so that electrons can move more efficiently in three-dimensional space, thereby reducing the migration resistance of electrons, improving the overall conductivity, and then accelerating the heating rate.

[0018] 3. The present invention prepares a three-dimensional boron nitride through a sodium chloride template, and performs silane coupling agent modification and carbon doping on the three-dimensional structure. Compared with the traditional two-dimensional structure, the three-dimensional structure can provide more heat conduction paths. After carbon doping, on the one hand, the introduction of carbon atoms will form a new heat conduction channel in the boron nitride lattice and enhance the thermal conductivity of the original channel. On the other hand, after the carbon atoms enter the boron nitride lattice, they will interact with boron atoms and nitrogen atoms, change the scattering mechanism of the lattice vibration, reduce phonon scattering, increase the mean free path of phonons for heat transfer, and thus improve the thermal conductivity. In addition, the arrangement of aluminum and oxygen atoms in the crystal structure of the modified nano-aluminum oxide is conducive to the transmission of phonons, and the three-dimensional structure of boron nitride provides a multi-directional propagation path for phonons. The combination of the two greatly improves the thermal conductivity efficiency, thereby effectively improving the thermal conductivity efficiency and achieving a rapid temperature rise effect.

[0019] 4. The surface properties of the nano-aluminum oxide and three-dimensional boron nitride modified by the silane coupling agent in the thermally conductive insulating layer of the present invention are changed, the charge active sites on the surface are reduced, and the conductivity of the material is reduced. At the same time, the polyimide network structure generated by the reaction of 4,4'-diaminodiphenyl ether and pyromellitic anhydride during the preparation process is wrapped around the thermally conductive filler, further enhancing the insulation performance. The polyimide network structure has a high resistivity and can effectively prevent the movement of electrons, thereby achieving a good electrical insulation effect. After being impregnated with the reaction glue and dried, the polymer in the reaction glue further fills the gaps between the fibers and undergoes a cross-linking reaction with the fibers to form a more compact and solid structure, thereby improving the structural stability of the thermally conductive insulating layer.

[0020] 5. In the preparation of the heat-insulating layer of the present invention, a heat-insulating gel is prepared by polymerizing benzophenone oxadiazine monomers and hydrolyzing tetraethyl orthosilicate, and then adding ZIF-L powder. The polymer and network structure formed after the polymerization of benzophenone oxadiazine monomers and the hydrolysis of tetraethyl orthosilicate have certain heat-insulating properties and can block the conduction of heat. The ZIF-L powder has a special microporous structure, and its pore size can effectively limit the thermal motion of gas molecules and reduce the heat transfer through gas convection and conduction. The ZIF-L powder and the polymer molecular chain produce physical adsorption or chemical bonding, which enhances the interaction force inside the gel. The ZIF-L powder is dispersed in the polymer and the network structure, which increases the tortuosity of the heat propagation path, thereby further enhancing the heat-insulating capacity of the entire gel system, so that the prepared heat-insulating layer can better block the diffusion of heat inside the hair straightener, reduce the loss of heat to the external environment, improve the thermal efficiency of the hair straightener, reduce energy waste, and prevent adverse effects such as burns on users due to overheating. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the invention and, together with the description, further serve to explain the principles of the invention and to enable those skilled in the relevant art to make and use the invention.

[0022] Figure 1 This is a process flow chart of a conductive heating plate for a hair straightener used in an embodiment of the present invention.

[0023] Figure 2 The present invention is a schematic structural diagram of a conductive heating plate for a hair straightener. DETAILED DESCRIPTION

[0024] The following is a detailed description of a preparation process of a conductive heating plate for a hair straightener provided by the present invention in conjunction with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods to implement some known technologies; and the accompanying drawings are only for more specific description of the embodiments, and are not intended to specifically limit the present invention.

[0025] Example 1 A preparation process for a conductive heating plate for a hair straightener, such as Figure 1-Figure 2 As shown, the following steps are included: S1: Preparation of graphene composite mixture S1.1: 2 parts by weight of polyvinyl alcohol and 0.3 parts by weight of sodium carboxymethyl cellulose are added to 80 parts by weight of deionized water, and then 0.2 parts by weight of sodium dodecylbenzene sulfonate are added, and the mixture is stirred at 80° C. for 2 hours to obtain a mixed solution; S1.2: Add 2 parts by weight of onion carbon and 5 parts by weight of modified graphene oxide to 50 parts by weight of N,N-dimethylamide, mix them by ultrasonic at room temperature for 30 minutes, then add 12 parts by weight of polyacrylonitrile, stir and mix at 60°C for 24 hours to obtain a conductive dispersion; S1.3: adding the conductive dispersion to the mixed solution, stirring and mixing at 70° C. for 6 h, and then cooling and standing for 24 h to obtain a graphene composite mixed solution; S2: Preparation of modified doped three-dimensional boron nitride S2.1: 12 parts by weight of saturated sodium chloride are added to 20 parts by weight of alcohol, and then vacuum filtered and dried to obtain micron sodium chloride crystals, 10 parts by weight of micron sodium chloride crystals and 2 parts by weight of boron trioxide are mixed and placed in an alumina crucible, and then the alumina crucible is placed in a tube furnace, argon gas is introduced, and heated to 500°C at 10°C / min; S2.2: After 500°C, turn off the argon gas, introduce ammonia, continue heating to 700°C, keep warm for 20 minutes, heat to 1100°C again, keep warm for 10 minutes, cool to room temperature, wash the precipitate with deionized water, then vacuum filter and dry, and dry at 60°C for 10 hours to obtain three-dimensional boron nitride; S2.3: 3 parts by weight of three-dimensional boron nitride are added to 10 parts by weight of anhydrous ethanol, and stirred at 50°C and 5000 r / min for 20 min under ultrasonic conditions, and then 0.2 parts by weight of a 20wt% silane coupling agent KH560 aqueous solution is added, and stirring is continued for 40 min, and then the mixture is placed in an oven to dry at 60°C, and ground to obtain a silane coupling agent-modified three-dimensional boron nitride; S2.4: Place the silane coupling agent modified three-dimensional boron nitride in a plasma reaction device, evacuate to -2800 kPa, then introduce ethylene and nitrogen to -2000 kPa, then evacuate to -2800 kPa again, then introduce ethylene and nitrogen to -1300 kPa, and finally evacuate to -2800 kPa again, and perform plasma discharge at 28 kV voltage and 9 kHz frequency for 15 minutes to obtain modified doped three-dimensional boron nitride, wherein the weight ratio of ethylene to nitrogen is 1:25; S3: Preparation of thermally conductive insulating layer S3.1: 0.02 parts by weight of silane coupling agent KH550 was added to 100 parts by weight of ethanol, and then glacial acetic acid was added dropwise to adjust the pH value to 3. After hydrolysis for 20 minutes, 2 parts by weight of nano-alumina was added, and ultrasonic mixing was performed for 1 hour, and stirred in a water bath at 70°C for 2 hours. After filtering, it was washed twice with anhydrous ethanol and dried to obtain modified nano-alumina; S3.2: Add 0.2 parts by weight of modified nano-aluminum trioxide and 0.5 parts by weight of modified doped three-dimensional structured boron nitride to 20 parts by weight of N, N'-dimethylacetamide solution, and mix under ultrasonic stirring for 8 hours. In a nitrogen atmosphere, add 1 part by weight of 4,4'-diaminodiphenyl ether, and mix under stirring for 20 minutes. Then, add 0.3 parts by weight of pyromellitic anhydride three times in an ice bath, and mix under stirring for 20 minutes. Then, obtain a spinning solution, and perform electrostatic spinning at a spinning voltage of 20 kV, a receiving distance of 20 cm, and a push injection speed of 0.8 mm / min to obtain a thermally conductive insulating spinning membrane; S3.3: Dissolve 2 parts by weight of 4,4'-diaminodiphenyl ether in 50 parts by weight of N,N'-dimethylacetamide solution, then add 2 parts by weight of pyromellitic anhydride, react for 4 hours to obtain a reaction glue solution, immerse the thermally conductive insulating spinning membrane in the reaction glue solution for 4 hours, and then vacuum dry to obtain a thermally conductive insulating film, i.e., a thermally conductive insulating layer; S4: Preparation of thermal insulation layer S4.1: 4 parts by weight of zinc nitrate hexahydrate and 16 parts by weight of 2-methylimidazole are added to 500 parts by weight of deionized water respectively, and the mixture is stirred and dissolved for 4 hours to obtain a zinc nitrate hexahydrate solution and a 2-methylimidazole solution; S4.2: Add the zinc nitrate hexahydrate solution to the 2-methylimidazole solution, continue stirring and mixing for 4 hours, then centrifuge at 8000 r / min, filter to obtain a precipitate, wash the precipitate with deionized water and dry to obtain ZIF-L powder; S4.3: Add 2 parts by weight of benzoxazine monomer to 60 parts by weight of N,N-dimethylformamide solution, stir to dissolve, then add 2 parts by weight of 2 mol / L hydrogen chloride solution, stir and mix for 10 minutes, then add 12 parts by weight of tetraethyl orthosilicate, continue to stir and mix for 20 minutes, finally add 0.2 parts by weight of ZIF-L powder, and ultrasonically disperse for 1 hour to obtain a thermal insulation gel solution; S4.4: inject the thermal insulation gel solution into a polypropylene tank to seal the gel, the gel time is 7 hours, and then age for 48 minutes, and finally perform solvent replacement and normal pressure drying to obtain the thermal insulation gel, which is the thermal insulation layer; S5: Preparation of conductive heating plate S5.1: The graphene composite mixed solution is electrospinned to form a composite film, wherein the distance between the needle tip and the collecting device is 15 cm, the voltage is 15 kV, and the injection speed is 0.5 mm / min. The composite film is then heated at 280°C for 2 h, and then kept at 700°C for 10 min in a nitrogen atmosphere to obtain a graphene composite heating layer; S5.2: Use an etcher to etch the designed circuit onto the conductor circuit layer, then print the cured electronic paste onto the circuit of the conductor circuit layer, and form a conductive layer after curing at 180°C for 10 minutes. Stack the ceramic substrate, thermal conductive insulation layer, graphene composite heating layer, conductive layer and thermal insulation layer in sequence from top to bottom and press them with a press to obtain a composite board. The pressing temperature is controlled at 300°C to obtain a conductive heating plate.

[0026] Example 2 A preparation process for a conductive heating plate for a hair straightener, such as Figure 1-Figure 2 As shown, the following steps are included: S1: Preparation of graphene composite mixture S1.1: 2 parts by weight of polyvinyl alcohol and 0.3 parts by weight of sodium carboxymethyl cellulose are added to 80 parts by weight of deionized water, and then 0.2 parts by weight of sodium dodecylbenzene sulfonate are added, and the mixture is stirred at 85° C. for 3 hours to obtain a mixed solution; S1.2: Add 2 parts by weight of onion carbon and 5 parts by weight of modified graphene oxide to 50 parts by weight of N,N-dimethylamide, mix them ultrasonically at room temperature for 40 minutes, then add 12 parts by weight of polyacrylonitrile, stir and mix at 65°C for 25 hours to obtain a conductive dispersion; S1.3: adding the conductive dispersion to the mixed solution, stirring and mixing at 75°C for 8 hours, and then cooling and standing for 25 hours to obtain a graphene composite mixed solution; S2: Preparation of modified doped three-dimensional boron nitride S2.1: 12 parts by weight of saturated sodium chloride are added to 20 parts by weight of alcohol, and then vacuum filtered and dried to obtain micron sodium chloride crystals, 10 parts by weight of micron sodium chloride crystals and 2 parts by weight of boron trioxide are mixed and placed in an alumina crucible, and then the alumina crucible is placed in a tube furnace, argon gas is introduced, and heated to 520°C at 12°C / min; S2.2: After 520°C, turn off the argon gas, introduce ammonia, continue heating to 720°C, keep warm for 30 minutes, heat to 1200°C again, keep warm for 20 minutes, cool to room temperature, wash the precipitate with deionized water, then vacuum filter and dry, and dry at 65°C for 12 hours to obtain three-dimensional boron nitride; S2.3: 3 parts by weight of three-dimensional boron nitride are added to 10 parts by weight of anhydrous ethanol, and stirred at 60°C and 6000 r / min for 30 minutes under ultrasonic conditions, and then 0.2 parts by weight of a 20wt% silane coupling agent KH560 aqueous solution is added, and stirring is continued for 50 minutes, and then the mixture is placed in an oven to dry at 70°C, and ground to obtain a silane coupling agent-modified three-dimensional boron nitride; S2.4: Place the silane coupling agent modified three-dimensional boron nitride in a plasma reaction device, evacuate to -3000 kPa, then introduce ethylene and nitrogen to -2200 kPa, then evacuate to -3000 kPa again, then introduce ethylene and nitrogen to -1500 kPa, and finally evacuate to -3000 kPa again, and perform plasma discharge at 30 kV voltage and 10 kHz frequency for 20 minutes to obtain modified doped three-dimensional boron nitride, wherein the weight ratio of ethylene to nitrogen is 1:25; S3: Preparation of thermally conductive insulating layer S3.1: 0.02 parts by weight of silane coupling agent KH550 was added to 100 parts by weight of ethanol, and then glacial acetic acid was added dropwise to adjust the pH value to 3. After hydrolysis for 30 minutes, 2 parts by weight of nano-alumina was added, and ultrasonic mixing was performed for 2 hours, and stirring was performed in a water bath at 80°C for 3 hours. After filtering, washing was performed with anhydrous ethanol for 3 times, and modified nano-alumina was obtained after drying; S3.2: Add 0.2 parts by weight of modified nano-aluminum trioxide and 0.5 parts by weight of modified doped three-dimensional structure boron nitride to 20 parts by weight of N, N'-dimethylacetamide solution, mix under ultrasonic stirring for 10 hours, add 1 part by weight of 4,4'-diaminodiphenyl ether under nitrogen atmosphere, stir and mix for 30 minutes, then add 0.3 parts by weight of pyromellitic anhydride three times under ice bath conditions, stir and mix for 30 minutes, and then obtain spinning solution, perform electrostatic spinning at a spinning voltage of 22 kV, a receiving distance of 22 cm, and a push injection speed of 0.9 mm / min to obtain a thermally conductive insulating spinning membrane; S3.3: Dissolve 2 parts by weight of 4,4'-diaminodiphenyl ether in 50 parts by weight of N,N'-dimethylacetamide solution, then add 2 parts by weight of pyromellitic anhydride, react for 5 hours to obtain a reaction glue solution, immerse the thermally conductive insulating spinning membrane in the reaction glue solution for 5 hours, and then vacuum dry to obtain a thermally conductive insulating film, i.e., a thermally conductive insulating layer; S4: Preparation of thermal insulation layer S4.1: 4 parts by weight of zinc nitrate hexahydrate and 16 parts by weight of 2-methylimidazole are added to 500 parts by weight of deionized water respectively, and the mixture is stirred and dissolved for 5 hours to obtain a zinc nitrate hexahydrate solution and a 2-methylimidazole solution; S4.2: Add zinc nitrate hexahydrate solution to 2-methylimidazole solution, continue stirring and mixing for 5 hours, then centrifuge at 9000 r / min, filter to obtain a precipitate, wash the precipitate with deionized water and dry to obtain ZIF-L powder; S4.3: Add 2 parts by weight of benzoxazine monomer to 60 parts by weight of N,N-dimethylformamide solution, stir to dissolve, then add 2 parts by weight of 2 mol / L hydrogen chloride solution, stir and mix for 12 minutes, then add 12 parts by weight of tetraethyl orthosilicate, continue stirring and mixing for 30 minutes, finally add 0.2 parts by weight of ZIF-L powder, and ultrasonically disperse for 2 hours to obtain a thermal insulation gel solution; S4.4: inject the thermal insulation gel solution into a polypropylene tank to seal the gel, the gel time is 8 hours, and then aged for 50 minutes, and finally the solvent is replaced and dried at normal pressure to obtain the thermal insulation gel, which is the thermal insulation layer; S5: Preparation of conductive heating plate S5.1: The graphene composite mixed solution is electrospinned to form a composite film, wherein the distance between the needle tip and the collecting device is 18 cm, the voltage is 16 kV, and the injection speed is 0.8 mm / min. The composite film is then heated at 300°C for 3 h, and then kept at 800°C for 12 min in a nitrogen atmosphere to obtain a graphene composite heating layer; S5.2: Use an etcher to etch the designed circuit onto the conductor circuit layer, then print the cured electronic paste onto the circuit of the conductor circuit layer, and form a conductive layer after curing at 200°C for 20 minutes. Stack the ceramic substrate, thermal conductive insulation layer, graphene composite heating layer, conductive layer and thermal insulation layer in sequence from top to bottom and press them with a press to obtain a composite board. The pressing temperature is controlled at 320°C to obtain a conductive heating plate.

[0027] Example 3 A preparation process for a conductive heating plate for a hair straightener, such as Figure 1-Figure 2 As shown, the following steps are included: S1: Preparation of graphene composite mixture S1.1: 3 parts by weight of polyvinyl alcohol and 0.5 parts by weight of sodium carboxymethyl cellulose are added to 100 parts by weight of deionized water, and then 0.3 parts by weight of sodium dodecylbenzene sulfonate are added, and the mixture is stirred at 80° C. for 2 hours to obtain a mixed solution; S1.2: 3 parts by weight of onion carbon and 8 parts by weight of modified graphene oxide are added to 60 parts by weight of N, N-dimethylamide, and ultrasonically mixed at room temperature for 30 minutes, and then 15 parts by weight of polyacrylonitrile are added, and stirred and mixed at 60°C for 24 hours to obtain a conductive dispersion; S1.3: adding the conductive dispersion to the mixed solution, stirring and mixing at 70° C. for 6 h, and then cooling and standing for 24 h to obtain a graphene composite mixed solution; S2: Preparation of modified doped three-dimensional boron nitride S2.1: 13 parts by weight of saturated sodium chloride is added to 22 parts by weight of alcohol, and then vacuum filtered and dried to obtain micron sodium chloride crystals, 12 parts by weight of micron sodium chloride crystals and 3 parts by weight of boron trioxide are mixed and placed in an alumina crucible, and then the alumina crucible is placed in a tube furnace, argon gas is introduced, and heated to 500°C at 10°C / min; S2.2: After 500°C, turn off the argon gas, introduce ammonia, continue heating to 700°C, keep warm for 20 minutes, heat to 1100°C again, keep warm for 10 minutes, cool to room temperature, wash the precipitate with deionized water, then vacuum filter and dry, and dry at 60°C for 10 hours to obtain three-dimensional boron nitride; S2.3: Add 5 parts by weight of three-dimensional boron nitride to 12 parts by weight of anhydrous ethanol, stir for 20 minutes at 50°C ultrasonic conditions and 5000 r / min, then add 0.3 parts by weight of a 30wt% silane coupling agent KH560 aqueous solution, continue stirring for 40 minutes, then place in an oven to dry at 60°C, grind and crush to obtain a silane coupling agent modified three-dimensional boron nitride; S2.4: Place the silane coupling agent modified three-dimensional boron nitride in a plasma reaction device, evacuate to -2800 kPa, then introduce ethylene and nitrogen to -2000 kPa, then evacuate to -2800 kPa again, then introduce ethylene and nitrogen to -1300 kPa, and finally evacuate to -2800 kPa again, and perform plasma discharge at 28 kV voltage and 9 kHz frequency for 15 minutes to obtain modified doped three-dimensional boron nitride, wherein the weight ratio of ethylene to nitrogen is 2:25; S3: Preparation of thermally conductive insulating layer S3.1: 0.05 parts by weight of silane coupling agent KH550 was added to 120 parts by weight of ethanol, and then glacial acetic acid was added dropwise to adjust the pH value to 4. After hydrolysis for 20 minutes, 3 parts by weight of nano-alumina was added, and ultrasonic mixing was performed for 1 hour, and stirred in a water bath at 70°C for 2 hours. After filtering, it was washed twice with anhydrous ethanol and dried to obtain modified nano-alumina; S3.2: Add 0.3 parts by weight of modified nano-aluminum trioxide and 0.7 parts by weight of modified doped three-dimensional structure boron nitride to 30 parts by weight of N, N'-dimethylacetamide solution, and mix under ultrasonic stirring for 8 hours. In a nitrogen atmosphere, add 2 parts by weight of 4,4'-diaminodiphenyl ether, and mix under stirring for 20 minutes. Then, add 0.5 parts by weight of pyromellitic anhydride three times in an ice bath, and mix under stirring for 20 minutes. Then, obtain a spinning solution, and perform electrostatic spinning at a spinning voltage of 20 kV, a receiving distance of 20 cm, and a push injection speed of 0.8 mm / min to obtain a thermally conductive insulating spinning membrane; S3.3: 3 parts by weight of 4,4'-diaminodiphenyl ether is dissolved in 60 parts by weight of N,N'-dimethylacetamide solution, and then 3 parts by weight of pyromellitic anhydride is added, and the reaction is carried out for 4 hours to obtain a reaction glue solution, and a thermally conductive insulating spinning membrane is immersed in the reaction glue solution for 4 hours, and then vacuum dried to obtain a thermally conductive insulating film, that is, a thermally conductive insulating layer; S4: Preparation of thermal insulation layer S4.1: 5 parts by weight of zinc nitrate hexahydrate and 18 parts by weight of 2-methylimidazole are added to 520 parts by weight of deionized water respectively, and the mixture is stirred and dissolved for 4 hours to obtain a zinc nitrate hexahydrate solution and a 2-methylimidazole solution; S4.2: Add the zinc nitrate hexahydrate solution to the 2-methylimidazole solution, continue stirring and mixing for 4 hours, then centrifuge at 8000 r / min, filter to obtain a precipitate, wash the precipitate with deionized water and dry to obtain ZIF-L powder; S4.3: Add 3 parts by weight of benzoxazine monomer to 70 parts by weight of N,N-dimethylformamide solution, stir to dissolve, then add 3 parts by weight of 2 mol / L hydrogen chloride solution, stir and mix for 10 minutes, then add 15 parts by weight of tetraethyl orthosilicate, continue to stir and mix for 20 minutes, finally add 0.5 parts by weight of ZIF-L powder, and ultrasonically disperse for 1 hour to obtain a thermal insulation gel solution; S4.4: inject the thermal insulation gel solution into a polypropylene tank to seal the gel, the gel time is 7 hours, and then age for 48 minutes, and finally perform solvent replacement and normal pressure drying to obtain the thermal insulation gel, which is the thermal insulation layer; S5: Preparation of conductive heating plate S5.1: The graphene composite mixed solution is electrospinned to form a composite film, wherein the distance between the needle tip and the collecting device is 15 cm, the voltage is 15 kV, and the injection speed is 0.5 mm / min. The composite film is then heated at 280°C for 2 h, and then kept at 700°C for 10 min in a nitrogen atmosphere to obtain a graphene composite heating layer; S5.2: Use an etcher to etch the designed circuit onto the conductor circuit layer, then print the cured electronic paste onto the circuit of the conductor circuit layer, and form a conductive layer after curing at 180°C for 10 minutes. Stack the ceramic substrate, thermal conductive insulation layer, graphene composite heating layer, conductive layer and thermal insulation layer in sequence from top to bottom and press them with a press to obtain a composite board. The pressing temperature is controlled at 300°C to obtain a conductive heating plate.

[0028] Comparative Example 1 Compared with Example 1, the difference of Comparative Example 1 is that, in Comparative Example 1, the graphene composite heating layer is replaced by a pure graphene layer, and the other steps remain unchanged to prepare the conductive heating plate, which is recorded as Comparative Example 1.

[0029] Comparative Example 2 Compared with Example 1, the difference of Comparative Example 2 is that the onion carbon in step S1.2 is removed in Comparative Example 2, and the other steps remain unchanged to prepare the conductive heating plate, which is recorded as Comparative Example 2.

[0030] Comparative Example 3 Compared with Example 1, the difference of Comparative Example 3 is that Comparative Example 3 removes step S2.4, replaces the modified doped three-dimensional structured boron nitride in step S3.2 with the three-dimensional structured boron nitride modified by a silane coupling agent, and prepares the conductive heating plate without changing the other steps, which is recorded as Comparative Example 3.

[0031] Comparative Example 4 Compared with Example 1, the difference of Comparative Example 4 is that Comparative Example 4 removes the modified doped three-dimensional structure boron nitride in step S2 and step S3.2, and the other steps remain unchanged to prepare the conductive heating plate, which is recorded as Comparative Example 4.

[0032] Comparative Example 5 Compared with Example 1, the difference of Comparative Example 5 is that Comparative Example 5 removes step S2, replaces the modified doped three-dimensional structured boron nitride in step S3.2 with conventional silane coupling agent KH560 modified nano boron nitride, and prepares the conductive heating plate without changing the other steps, which is recorded as Comparative Example 5.

[0033] Comparative Example 6 Compared with Example 1, the difference of Comparative Example 6 is that the modified nano-aluminum oxide in step S3.1 and step S3.2 is removed, and the other steps remain unchanged to prepare the conductive heating plate, which is recorded as Comparative Example 6.

[0034] Comparative Example 7 Compared with Example 1, the difference of Comparative Example 7 is that Comparative Example 7 removes the ZIF-L powder in steps S4.1-S4.2 and step S4.3, and the remaining steps remain unchanged to prepare the conductive heating plate, which is recorded as Comparative Example 7.

[0035] The conductive heating plates prepared in Examples 1-3 and Comparative Examples 1-7 are assembled into a hair straightener to obtain a hair straightener.

[0036] The measuring end of the thermocouple is tightly attached to the surface of the conductive heating plate of the hair straighteners of Examples 1-3 and Comparative Examples 1-6 to ensure good thermal contact. The wire of the thermocouple is connected to the temperature measuring instrument to read the displayed temperature value. The hair straightener is then plugged in for use. When the temperature value is displayed as 200° C., the time used is measured. The average value is taken after three measurements. The measurement results are shown in Table 1.

[0037] Table 1. Time used for heating to 200°C for Examples 1-3 and Comparative Examples 1-5

[0038] It can be seen from the data in Table 1 that the data of Comparative Examples 1 and 2 have increased compared to the embodiment, indicating that graphene and onion carbon doped polyacrylonitrile carbonized fiber can speed up the heating speed compared to the pure graphene heating layer, and improve the user experience without preheating. It can be seen from the data in Comparative Examples 3-6 that the carbon-doped three-dimensional structured boron nitride interacts with the modified nano-aluminum oxide, and the combination of the two greatly improves the thermal conductivity, thereby effectively improving the thermal conductivity and achieving the effect of rapid heating.

[0039] The hair straighteners assembled in Examples 1-3 were subjected to frequent heating and cooling cycles 10 times, and then used again to measure the time taken to heat to 200° C. The measurement results are shown in Table 2.

[0040] Table 2. The time used for heating to 160°C for 10 cycles in Examples 1-3

[0041] It can be seen from the data in Table 2 that during the frequent heating and cooling cycles of the hair straightener, the performance of the conductive heating plate remains unchanged and a good heating speed can be maintained.

[0042] The measuring end of the thermocouple is tightly attached to the surface of the outer shell of the hair straightener of Examples 1-3 and Comparative Example 7 to ensure good thermal contact. The wire of the thermocouple is connected to the temperature measuring instrument to read the displayed temperature value. The hair straightener is then plugged in for use. The outer shell temperature of the hair straightener is measured during use. The average value is obtained by measuring three times. The measurement results are shown in Table 3.

[0043] Table 3. Shell temperature of Examples 1-3 and Comparative Example 7

[0044] It can be seen from the data in Table 3 that the addition of ZIF-L powder can improve the thermal insulation capacity of the entire gel system.

[0045] The measuring end of the thermocouple is tightly attached to the surface of the thermal insulation layer of the conductive heating plate prepared in Example 1-3 to ensure good thermal contact. The wire of the thermocouple is connected to the temperature measuring instrument to read the displayed temperature value. Then, the conductive heating plate is heated to 350°C, and the surface temperature of the thermal insulation layer is measured. The average value is taken after three measurements. The measurement results are shown in Table 4.

[0046] Table 4. Surface temperature of thermal insulation layer of Examples 1-3

[0047] It can be seen from the data in Table 4 that the thermal insulation layer can achieve good thermal insulation effect. The thermal insulation layer can separate the conductive heating plate from the plastic material that fixes the heating plate, thereby preventing the conductive heating plate from being overheated and easily burning the plastic material that fixes the heating plate, causing the heating plate to fall off.

[0048] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A process for preparing a conductive heating plate for a hair straightener, characterized in that: The steps include: S1: Preparation of graphene composite mixture Polyvinyl alcohol, sodium carboxymethyl cellulose and sodium dodecylbenzene sulfonate are used as a mixed liquid, and then a conductive dispersion prepared by onion carbon, modified graphene oxide and polyacrylonitrile is added, and the graphene composite mixed liquid is prepared after mixing; S2: Preparation of modified doped three-dimensional boron nitride A three-dimensional boron nitride is prepared by using a sodium chloride template, the three-dimensional boron nitride is modified by a silane coupling agent, and then modified by plasma carbon doping to obtain a modified doped three-dimensional boron nitride; S3: Preparation of thermally conductive insulating layer The modified nano-aluminum oxide and the modified doped three-dimensional structured boron nitride are used as thermal conductive fillers, and then 4,4'-diaminodiphenyl ether and pyromellitic anhydride are added to prepare a spinning solution for electrostatic spinning to obtain a thermal conductive insulating spinning membrane, which is then immersed in a reaction glue solution composed of 4,4'-diaminodiphenyl ether, N,N'-dimethylacetamide solution and pyromellitic anhydride, and finally vacuum dried to obtain a thermal conductive insulating film, i.e., a thermal conductive insulating layer; S4: Preparation of thermal insulation layer The thermal insulation gel is prepared by using benzophenone oxadiazine monomer, ZIF-L powder and tetraethyl orthosilicate as raw materials, namely the thermal insulation layer; S5: Preparation of conductive heating plate A graphene composite heating layer is prepared by using a graphene composite mixed liquid, and a ceramic substrate, a thermal conductive insulating layer, a graphene composite heating layer, a conductive layer and a thermal insulating layer are stacked in sequence from bottom to top and pressed with a pressing machine to obtain a conductive heating plate.

2. The process for preparing a conductive heating plate for a hair straightener according to claim 1, characterized in that: Step S1: Preparation of graphene composite mixed solution, specifically comprising the following steps: S1.1: Add 2-3 parts by weight of polyvinyl alcohol and 0.3-0.5 parts by weight of sodium carboxymethyl cellulose to 80-100 parts by weight of deionized water, and then add 0.2-0.3 parts by weight of sodium dodecylbenzene sulfonate, and stir and mix at 80-85° C. for 2-3 hours to obtain a mixed solution; S1.2: Add 2-3 parts by weight of onion carbon and 5-8 parts by weight of modified graphene oxide to 50-60 parts by weight of N,N-dimethylamide, mix them ultrasonically at room temperature for 30-40 minutes, then add 12-15 parts by weight of polyacrylonitrile, stir and mix at 60-65°C for 24-25 hours to obtain a conductive dispersion; S1.3: Add the conductive dispersion into the mixed solution, stir and mix at 70-75°C for 6-8h, then cool and let stand for 24-25h to obtain a graphene composite mixed solution.

3. The process for preparing a conductive heating plate for a hair straightener according to claim 2, characterized in that: Step S2: Preparation of modified doped three-dimensional structured boron nitride, specifically comprising the following steps: S2.1: 12-13 parts by weight of saturated sodium chloride is added to 20-22 parts by weight of alcohol, and then vacuum filtered and dried to obtain micron sodium chloride crystals, 10-12 parts by weight of micron sodium chloride crystals and 2-3 parts by weight of boron trioxide are mixed and placed in an alumina crucible, and then the alumina crucible is placed in a tube furnace, argon gas is introduced, and heated to 500-520°C at 10-12°C / min; S2.2: After 500-520°C, turn off the argon gas, introduce ammonia, continue heating to 700-720°C, keep warm for 20-30 minutes, heat again to 1100-1200°C, keep warm for 10-20 minutes, cool to room temperature, wash the obtained precipitate with deionized water, then vacuum filter and dry, and dry at 60-65°C for 10-12 hours to obtain three-dimensional boron nitride; S2.3: Add 3-5 parts by weight of three-dimensional boron nitride to 10-12 parts by weight of anhydrous ethanol, stir for 20-30 minutes at 50-60°C under ultrasonic conditions and 5000-6000 r / min, then add 0.2-0.3 parts by weight of 20-30wt% silane coupling agent KH560 aqueous solution, continue stirring for 40-50 minutes, then place in an oven at 60-70°C to dry, grind and crush to obtain silane coupling agent modified three-dimensional boron nitride; S2.4: Place the silane coupling agent modified three-dimensional boron nitride in a plasma reaction device, evacuate to -2800 kPa to -3000 kPa, then introduce ethylene and nitrogen to -2000 kPa to -2200 kPa, then evacuate to -2800 kPa to -3000 kPa again, then introduce ethylene and nitrogen to -1300 kPa to -1500 kPa, finally evacuate to -2800 kPa to -3000 kPa again, and perform plasma discharge at a voltage of 28-30 kV and a frequency of 9-10 kHz for 15-20 minutes to obtain modified doped three-dimensional boron nitride.

4. The process for preparing a conductive heating plate for a hair straightener according to claim 3, characterized in that: Step S2.4: The weight ratio of ethylene to nitrogen is 1-2:

25.

5. The process for preparing a conductive heating plate for a hair straightener according to claim 3, characterized in that: Step S3: Preparation of the thermally conductive insulating layer, specifically comprising the following steps: S3.1: Add 0.02-0.05 parts by weight of silane coupling agent KH550 to 100-120 parts by weight of ethanol, then add glacial acetic acid to adjust the pH value to 3-4, hydrolyze for 20-30 minutes, add 2-3 parts by weight of nano-alumina, mix by ultrasonic for 1-2 hours, and stir in a water bath at 70-80°C for 2-3 hours, filter, wash with anhydrous ethanol 2-3 times, and dry to obtain modified nano-alumina; S3.2: Add 0.2-0.3 parts by weight of modified nano-aluminum trioxide and 0.5-0.7 parts by weight of modified doped three-dimensional structure boron nitride to 20-30 parts by weight of N, N'-dimethylacetamide solution, and mix under ultrasonic stirring for 8-10 hours. In a nitrogen atmosphere, add 1-2 parts by weight of 4,4'-diaminodiphenyl ether, and mix under stirring for 20-30 minutes. Then, add pyromellitic anhydride three times under ice bath conditions, adding 0.3-0.5 parts by weight of pyromellitic anhydride each time, and mix under stirring for 20-30 minutes to obtain a spinning solution. Perform electrostatic spinning at a spinning voltage of 20-22 kV, a receiving distance of 20-22 cm, and a push injection speed of 0.8-0.9 mm / min to obtain a thermally conductive insulating spinning membrane; S3.3: Dissolve 2-3 parts by weight of 4,4'-diaminodiphenyl ether in 50-60 parts by weight of N,N'-dimethylacetamide solution, then add 2-3 parts by weight of isophthalic anhydride, react for 4-5 hours to obtain a reaction colloid, immerse the thermally conductive insulating spinning membrane in the reaction colloid for 4-5 hours, and then vacuum dry it to obtain a thermally conductive insulating film, which is the thermally conductive insulating layer.

6. The process for preparing a conductive heating plate for a hair straightener according to claim 5, characterized in that: Step S4: Preparation of the heat-insulating layer, specifically comprising the following steps: S4.1: 4-5 parts by weight of zinc nitrate hexahydrate and 16-18 parts by weight of 2-methylimidazole are added to 500-520 parts by weight of deionized water respectively, and the mixture is stirred and dissolved for 4-5 hours to obtain a zinc nitrate hexahydrate solution and a 2-methylimidazole solution; S4.2: Add the zinc nitrate hexahydrate solution to the 2-methylimidazole solution, continue stirring and mixing for 4-5 hours, then centrifuge at 8000-9000 r / min, filter to obtain a precipitate, wash the precipitate with deionized water and dry to obtain ZIF-L powder; S4.3: Add 2-3 parts by weight of benzoxazine monomer to 60-70 parts by weight of N,N-dimethylformamide solution, stir to dissolve, then add 2-3 parts by weight of 2 mol / L hydrogen chloride solution, stir and mix for 10-12 minutes, then add 12-15 parts by weight of tetraethyl orthosilicate, continue to stir and mix for 20-30 minutes, finally add 0.2-0.5 parts by weight of ZIF-L powder, and ultrasonically disperse for 1-2 hours to obtain a thermal insulation gel solution; S4.4: Inject the thermal insulation gel solution into a polypropylene tank to seal the gel. The gel time is 7-8 hours, followed by aging for 48-50 minutes. Finally, solvent replacement and normal pressure drying are performed to obtain the thermal insulation gel, which is the thermal insulation layer.

7. The process for preparing a conductive heating plate for a hair straightener according to claim 6, characterized in that: Step S5: Preparation of the conductive heating plate, specifically comprising the following steps: S5.1: The graphene composite mixed solution is electrospinned to form a composite film, wherein the distance between the needle tip and the collecting device during electrospinning is 15-18 cm, the voltage is 15-16 kV, and the injection speed is 0.5-0.8 mm / min. The composite film is then heated at 280-300° C. for 2-3 h, and then kept at 700-800° C. for 10-12 min in a nitrogen atmosphere to obtain a graphene composite heating layer; S5.2: Use an etcher to etch the designed circuit onto the conductor circuit layer, then print the cured electronic paste onto the circuit of the conductor circuit layer, and form a conductive layer after curing at 180-200℃ for 10-20min. Stack the ceramic substrate, thermal conductive insulation layer, graphene composite heating layer, conductive layer and thermal insulation layer in sequence from top to bottom and press them with a press to obtain a composite board. The pressing temperature is controlled at 300-320℃ to obtain a conductive heating plate.

8. The process for preparing a conductive heating plate for a hair straightener according to claim 7, characterized in that: The ceramic substrate in step S5.2 is one of an aluminum oxide ceramic substrate and an aluminum nitride ceramic substrate.

9. The process for preparing a conductive heating plate for a hair straightener according to claim 7, characterized in that: In step S5.2, the conductor line layer is made of one of copper, aluminum, copper foil and aluminum foil materials.

10. A conductive heating plate for a hair straightener, characterized in that: The conductive heating plate is prepared by the preparation process of a conductive heating plate for a hair straightener as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method and device for heating a surface

    CN107006075A

  • Instantaneous heating panel and preparation method therefor

    CN107613588A

  • Benzoxazine resin-based high-power carbon crystal electric heating plate as well as preparation method and application thereof

    CN111642037A

  • Onion carbon / cured fiber composite material and preparation method and application thereof, composite electrothermal film and preparation method and application thereof

    CN114775094A

  • Heat-conducting aluminum-based copper-clad plate and preparation method thereof

    CN116476467A